2021
DOI: 10.1002/ece3.7972
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature increases reproductive investment in less preferred mates in the invasive European corn borer moth

Abstract: Rapidly changing environments may weaken sexual selection and lead to indiscriminate mating by interfering with the reception of mating signals or by increasing the costs associated with mate choice. If temperature alters sexual selection, it may impact population response and adaptation to climate change. Here, we examine how differences in temperature of the mating environment influence reproductive investment in the European corn borer moth (Ostrinia nubilalis). Mate preference in this species is known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 82 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Though warmer rearing temperatures did not change the overall strength of sexual isolation between populations, asymmetric contributions to total sexual isolation under warming conditions could facilitate asymmetric gene flow. While the causal mechanisms are unknown, a study in European corn borer moths similarly found a higher potential for gene flow under warmer rearing temperatures (Enos & Kozak, 2021). Sexual isolation may be particularly sensitive to environmental changes when differences in mating preferences and traits evolved due to environmental differences (Fisher et al, 2006; Lackey & Boughman, 2013; Seehausen et al, 1997; Ward & Blum, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though warmer rearing temperatures did not change the overall strength of sexual isolation between populations, asymmetric contributions to total sexual isolation under warming conditions could facilitate asymmetric gene flow. While the causal mechanisms are unknown, a study in European corn borer moths similarly found a higher potential for gene flow under warmer rearing temperatures (Enos & Kozak, 2021). Sexual isolation may be particularly sensitive to environmental changes when differences in mating preferences and traits evolved due to environmental differences (Fisher et al, 2006; Lackey & Boughman, 2013; Seehausen et al, 1997; Ward & Blum, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such changes could potentially increase, decrease, or have no effect on gene flow between populations (García‐Roa et al, 2020; Larson et al, 2019). However, two recent examples in insects found warmer temperatures caused higher mating rates between populations (Enos & Kozak, 2021; Kindle et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature and low-temperature stress irreversibly damages the function and structure of the reproductive system, thus, affecting the mating behavior of ectotherms (Singh et al, 2015;Enos and Kozak, 2021). High and low temperatures affect the mating behavior of fruit flies, including the mating-related traits of mating latency, duration of copulation, mating frequency, the number of progeny produced, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has found that when E and Z strain individuals are given the opportunity to mate with access only to water at standard temperatures (22–24 °C), females are more likely to mate with males of their own strain and females lay more egg clusters with preferred males (Liebherr and Roelofs 1975, Pélozuelo et al 2007, Dopman et al 2010, Enos and Kozak 2021). When exposed to elevated temperatures (above 27 °C) with access only to water, previous work found that mating pairs show patterns consistent with terminal investment of resources to reproduction: females lay more eggs earlier in life independent of the strain of the mate (Lee and Spence 1987, Enos and Kozak 2021). Building on this prior work, we provided adult corn borer moths access to supplemental sugar solutions during mating, at both ambient (23 °C) and elevated (28 °C) temperature.…”
Section: Introductionmentioning
confidence: 99%